Origins and Development of Schizophrenia: Advances in Experimental Psychopathology.
DOI: 10.1037/10305-011
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive vulnerability factors for schizophrenia: Convergence across genetic risk studies and longitudinal trait–state studies.

Abstract: ne prominent emphasis in attempts to understand the pathogen-0 esis of schizophrenia involves the search for factors in genetic proneness or vulnerability to schizophrenia. Although the evidence for genetic factors in schizophrenia is overwhelming, the nature of heritable components to schizophrenia has remained elusive (Gottesman & Shields, 1982;Kendler & Diehl, 1993). Part of the problem may be that it is not schizophrenia itself that is heritable but that several underlying factors associated with vulnerabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 42 publications
3
26
0
Order By: Relevance
“…Particularly rapid decreases in signal/ noise discrimination during vigilance can be created by burdening early perceptual encoding through substantial blurring (degrading) of single digit stimuli (Nuechterlein et al 1983). Consistent with these findings, a metaanalysis concluded that sustained attention demand can be increased by either sensory-perceptual load (degree of stimulus unfamiliarity) or working memory load (Braff 1993;Cornblatt and Keilp 1994;Nuechterlein 1991Nuechterlein , 1998Nuechterlein , 1995. Deficits in detection of target stimuli within a continuous series of briefly presented stimuli have been found among symptomatic chronic schizophrenia patients using standard and working memory burden versions (Bowen et al 1994;Cornblatt et al 1989;Ito et al 1997;Orzack and Kornetsky 1966;Seidman et al 1998;Walker 1981).…”
Section: Continuous Performance Taskmentioning
confidence: 91%
“…Particularly rapid decreases in signal/ noise discrimination during vigilance can be created by burdening early perceptual encoding through substantial blurring (degrading) of single digit stimuli (Nuechterlein et al 1983). Consistent with these findings, a metaanalysis concluded that sustained attention demand can be increased by either sensory-perceptual load (degree of stimulus unfamiliarity) or working memory load (Braff 1993;Cornblatt and Keilp 1994;Nuechterlein 1991Nuechterlein , 1998Nuechterlein , 1995. Deficits in detection of target stimuli within a continuous series of briefly presented stimuli have been found among symptomatic chronic schizophrenia patients using standard and working memory burden versions (Bowen et al 1994;Cornblatt et al 1989;Ito et al 1997;Orzack and Kornetsky 1966;Seidman et al 1998;Walker 1981).…”
Section: Continuous Performance Taskmentioning
confidence: 91%
“…There is substantial evidence that measures of sustained attention or vigilance, verbal declarative memory and working memory are valid endophenotypes in schizophrenia. Continuous performance tests (CPTs) are widely used measures of deficits in sustained, focused attention and are prominent indices of neurocognitive deficits in schizophrenia (50)(51)(52)(53). Deficits in detection of target stimuli are evident in CPT simple simultaneous discrimination and successive discrimination (54)(55)(56)(57)(58)(59).…”
Section: Neurocognitive Endophenotypesmentioning
confidence: 99%
“…[251][252][253] There is remarkable agreement in the literature that deficits in multiple cognitive domains predate the onset of clinical symptoms; [254][255][256][257][258] are not attributable to antipsychotic medications; 259 persist over the course of the illness; are unrelated to its duration; [260][261][262] and behave like a stable trait. 233,263,264 Pervasive cognitive dysfunction has been reported in > 50% of schizophrenia patients in a community-based survey in Scotland, 265 and there…”
Section: Cognitive Dysfunction As An Endophenotypementioning
confidence: 99%
“…Subtyping schizophrenia A Jablensky 823 205 Prepulse inhibition of the startle reflex [206][207][208] Deficient gating of the auditory evoked response (P50) [209][210][211] P300 amplitude reduction and latency delay 212 N400 amplitude reduction (semantic context underutilization) 213 Mismatch negativity (MMN) [214][215][216][217] Smooth pursuit eye movement dysfunction (SPEM) [218][219][220][221] Antisaccade error rate (AS) [222][223][224] Composite inhibitory phenotype (P50, AS, SPEM) 225 Multivariate electrophysiological endophenotype (MMN, P50, P300, AS) 226 Neuroimaging markers and endophenotypes Fronto-thalamic-cerebellar gray matter deficit 227 Fronto-striato-thalamic gray matter deficit 228 MRI-derived three-factor phenotype 229 MRI whole-brain nonlinear pattern classification 230 Frontal hypoactivation in response to cognitive tasks (hypofrontality) 231 Atrophic and static (neurodevelopmental) schizophrenia endophenotypes 232 Cognitive markers and endophenotypes Continuous performance tests (CPT, signal/noise ratio) [233][234][235] Attention and vigilance-based subtype 18 Verbal dysmnesic subtype 18 Verbal memory deficit, cortical or subcortical type 236,237 Dysexecutive subtype 18 Prefrontal executive/working memory phenotype 238 Frontal/abstraction deficit profile 239 Spatial working memory 240...…”
Section: Molecular Psychiatrymentioning
confidence: 99%